2006
DOI: 10.1055/s-2006-942384
|View full text |Cite
|
Sign up to set email alerts
|

Direct Acylation of Phenol and Naphthol Derivatives in a Mixture of Graphite and Methanesulfonic Acid

Abstract: Graphite in methanesulfonic acid is used to prepare o-hydroxyketones by direct acylation of phenol and naphthol derivatives with carboxylic acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…1-[2-Hydroxy-4-(prop-2-yn-1-yloxy)phenyl]ethanone (3) was subjected to condensation -cyclisation process with phenacyl bromide (5) in the presence of potassium carbonate with formation of [3-methyl-6-(prop-2-yn-1-yloxy)benzofuran-2-yl]-(phenyl)methanone (6) [12]. Some aliphatic and aromatic oxime intermediates 7a-7p were synthesized according to the presented earlier methods [13]. Alkyl oximes were synthesized by heating their precursors, alkyl aldehyde, with hydroxyl amine hydrochloride in presence of sodium acetate in MeOH at room temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1-[2-Hydroxy-4-(prop-2-yn-1-yloxy)phenyl]ethanone (3) was subjected to condensation -cyclisation process with phenacyl bromide (5) in the presence of potassium carbonate with formation of [3-methyl-6-(prop-2-yn-1-yloxy)benzofuran-2-yl]-(phenyl)methanone (6) [12]. Some aliphatic and aromatic oxime intermediates 7a-7p were synthesized according to the presented earlier methods [13]. Alkyl oximes were synthesized by heating their precursors, alkyl aldehyde, with hydroxyl amine hydrochloride in presence of sodium acetate in MeOH at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Attachment of other heterocyclic rings to benzofuran may lead to compounds of even higher activity against bacteria resistant to other drugs [7]. A number of natural and synthetic isoxazole based analogues such as ibotenic acid [8][9][10], muscimol [11] and some more exhibited valuable biological activities. Motivated by the above information on benzofuran and isoxazole derivatives, we have synthesized conjugated benzofuran-isoxazole derivatives targeting the potential pharmacophores.…”
Section: Introductionmentioning
confidence: 99%
“…18 However, a previous study reported that mainly o-acylated isomer was afforded by the treatment of m-cresol and carboxylic acid with graphite and methanesulfonic acid at 120 °C in several hours. 19 On the other hand, our conditions, which were carried out at room temperature, afforded 4-and 6-acetylated isomers with a 1.4~2 : 1 ratio . The reaction condition can be applied to various carbon chains of macyloxy toluenes in good yield (Table 3, entry 4). 4-Fluoro-, 4-chloro-and 4-bromo-phenylacetate or phenylbenzoate have to heated at 60°C in neat TfOH to achieve Fries rearrangements in good yield (Table 3 entries 5-7).…”
Section: Fries Rearrangements Of O-acyloxy Benzenesmentioning
confidence: 88%
“…The following compounds obtained in this paper are known compounds: 2‐bromophenyl acetate8k ( 1 ), 2‐methoxyphenyl acetate18 ( 2 ), 2‐nitrophenyl acetate19 ( 3 ), 2,4‐dimethylphenyl acetate20 ( 4 ), 3‐tolyl acetate21 ( 5 ), 3,5‐dimethylphenyl acetate22 ( 6 ), 3‐fluorophenyl acetate23 ( 7 ), 4‐benzylphenyl acetate24 ( 8 ), 4‐bromophenyl acetate25a ( 9 ), 4‐chlorophenyl acetate25b ( 10 ), 4‐ tert ‐butylphenyl acetate8i ( 11 ), 4‐nitrophenyl acetate26 ( 12 ), naphthalen‐1‐yl acetate6e ( 13 ), naphthalen‐2‐yl acetate27 ( 14 ), phenyl acetate6e ( 15 ), 8‐hydroxy‐9,10‐dioxo‐9,10‐dihydroanthracen‐1‐yl acetate28 ( 16 ), 4‐methoxyphenyl acetate29 ( 17 ), (4‐chlorophenyl)(diethoxyphosphoryl)methyl acetate30a ( 18 ), (diethoxyphosphoryl)( p ‐tolyl)methyl acetate30a ( 19 ), (diethoxyphosphoryl)( m ‐tolyl)methyl acetate30a ( 20 ), (diethoxyphosphoryl)(phenyl)methyl acetate30a ( 21 ), acetic acid 10,13‐dimethyl‐17‐octyl‐2,3,4,7,8,9,10,11,12,13,14,15,16,17‐tetradecahydro‐1 H ‐cyclopenta[ a ]phenanthren‐3‐yl ester31 ( 22 ), acetic acid 2‐oxo‐1,2‐diphenylethyl ester30b ( 23 ), (1 R ,2 R ,5 R )‐2‐isopropyl‐5‐methylcyclohexyl acetate32 ( 24 ), 1‐phenylethyl acetate33 ( 25 ), benzyl acetate32 ( 26 ), 2‐nitrobenzyl acetate34 ( 27 ), acetic acid dodecyl ester35 ( 28 ), 2‐methyl‐1‐phenylpropan‐2‐yl acetate32 ( 29 ), 4‐methoxyphenyl benzoate36 ( 30 ), 4‐chlorophenyl benzoate36 ( 31 ), dodecyl benzoate37 ( 32 ), 4‐methoxyphenyl 2‐chlorobenzoate38 ( 33 ), 4‐methoxyphenyl 2‐phenylacetate39 ( 34 ), 4‐methoxyphenyl 4‐methylbenzoate40 ( 35 ), phenyl 2‐chloroacetate41 ( 36 ), 4‐methoxyphenyl thiophene‐2‐carboxylate42 ( 37 ), 3,6,9,12‐tetraoxa‐18‐azabicyclo[12.3.1]octadeca‐1(18),14,16‐triene‐2,13‐dione43 ( 38 ), N ‐phenylacetamide26 ( 39 ), N ‐(2‐cyanophenyl)acetamide44 ( 40 ), N ‐(4‐bromophenyl)acetamide43 ( 41 ), N ‐(4‐nitrophenyl)acetamide26 ( 42 ), N ‐(4‐cyanophenyl)acetamide45 ( 43 ), N ‐(2‐chlorophenyl)acetamide46 ( 44 ), N ‐(3‐hydroxyphenyl)acetamide47a ( 45 ), N ‐(4‐acetylphenyl)acetamide47b ( 46 ), 2‐acetamidobenzoic acid48 ( 47 ), 5‐acetamido‐2‐hydroxybenzoic acid49 ( 48 ), N ‐(3‐bromophenyl)acetamide50 ( 49 ), N‐o ‐tolylacetamide…”
Section: Methodsmentioning
confidence: 99%